Characteristics of Breast Cancer at Royal Prima Hospital, Medan, 2020-2025 - Grace Dewani Silaban; Yeni Puspawani; Yolanda Eliza Putri Lubis (International Journal of Health and Pharmaceutical (IJHP), 2025)
Background: Breast cancer represents a significant global health burden, particularly in Southeast Asian populations. This study characterizes breast cancer patients in a North Sumatran tertiary hospital. Objectives: To describe demographic characteristics, histopathological classification, and clinical outcomes of breast cancer patients. Methods: A retrospective descriptive cross-sectional study was conducted at Royal Prima Hospital Medan using total enumeration sampling of 19 breast cancer patients with complete medical records from 2020 to 2025. Data on age, gender, histopathological type, and hospitalization duration were extracted from medical records. Descriptive statistics using SPSS software analyzed frequency distributions and percentages. Results: Nineteen patients demonstrated a mean age of 49.3 years, predominantly pre-elderly females (78.95%). Invasive ductal carcinoma and invasive lobular carcinoma were the main histological types. Mean hospitalization duration was 7.5 days, ranging from 2 to 18 days, influenced by surgical complexity and postoperative complications, including seroma formation and wound dehiscence. Conclusion: This institutional characterization provides baseline epidemiological data on breast cancer presentations, emphasizing the need for enhanced screening, early detection programs, and optimized surgical management protocols to improve outcomes.